Biosecurity and Emergency Preparedness - Azwana,; Thanh Nguyen, Phong; Lydia, E. Laxmi; Shankar, K.; Rahim, Robbi (International Journal of Psychosocial Rehabilitation, 2024)
To reduce the infectious disease transmission risk in livestock and crops, quarantined pests, living modified organisms, and invasive alien species, an originally conceptualized set of preventive measures designed is known as biosecurity. Some risks are growing rapidly. Because of limitations in available resources and time for calculating the likelihood and analyzing threats of the occurrence, developing an effective policy is a major challenge. The emergencies in biosecurity can occur through weeds, pests, and diseases; these are having a negative impact on the community, economy, and environment. Commonly occurring incidents that are within the capacity of the NSW Department of Primary Industries (DPI) are not included in biosecurity emergencies.